Ferric reduction by a CYBDOM protein counteracts increased iron availability in root meristems induced by phosphorus deficiency - Rodolfo A. Maniero; Cristiana Picco; Anja Hartmann; Felipe Engelberger; Antonella Gradogna; Joachim Scholz-Starke; Michael Melzer; Georg Künze; Armando Carpaneto; Nicolaus von Wirén; Ricardo F. H. Giehl (Nature Communications, 2024)
Abstract To mobilize sparingly available phosphorus (P) in the rhizosphere, many plant species secrete malate to release P sorbed onto (hydr)oxides of aluminum and iron (Fe). In the presence of Fe, malate can provoke Fe over-accumulation in the root apoplast, triggering a series of events that inhibit root growth. Here, we identified HYPERSENSITIVE TO LOW P1 (HYP1), a CYBDOM protein constituted of a DOMON and a cytochrome b561 domain, as critical to maintain cell elongation and meristem integrity under low P. We demonstrate that HYP1 mediates ascorbate-dependent trans-plasma membrane electron transport and can reduce ferric and cupric substrates in Xenopus laevis oocytes and in planta. HYP1 expression is up-regulated in response to P deficiency in the proximal zone of the root apical meristem. Disruption of HYP1 leads to increased Fe and callose accumulation in the root meristem and causes significant transcriptional changes in roots. We further demonstrate that HYP1 activity overcomes malate-induced Fe accumulation, thereby preventing Fe-dependent root growth arrest in response to low P. Collectively, our results uncover an ascorbate-dependent metalloreductase that is critical to protect root meristems of P-deficient plants from increased Fe availability and provide insights into the physiological function of the yet poorly characterized but ubiquitous CYBDOM proteins.